Enhancing virtual reality exposure therapy: Optimizing treatment outcomes for agoraphobia through advanced simulation and comparative analysis - Yang, Jackson; Che, Xiaoping; Qu, Chenxin; Di, Xiaofei; Liu, Haiming (Computer animation and virtual worlds, 2024)
This paper investigates the application of Virtual Reality Exposure Therapy (VRET) to treat agoraphobia, focusing on two pivotal research questions derived from identified gaps in current therapeutic approaches. The first question (RQ1) addresses the development of complex VR environments to enhance therapy's effectiveness by simulating real‐world anxiety triggers. The second question (RQ2) examines the differential impact of these VR environments on agoraphobic and nonagoraphobic participants through rigorous comparative analyses using t‐tests. Methodologies include advanced data processing techniques for electrodermal activity (EDA) and eye‐tracking metrics to assess the anxiety levels induced by these environments. Additionally, qualitative methods such as structured interviews and questionnaires complement these measurements, providing deeper insights into the subjective experiences of participants. Video recordings of sessions using Unity software offer a layer of data, enabling the study to replay and analyze interactions within the VR environment meticulously. The experimental results confirm the efficacy of VR settings in eliciting significant physiological and psychological responses from participants, substantiating the VR scenarios' potential as a therapeutic tool. This study contributes to the broader discourse on the viability and optimization of VR technologies in clinical settings, offering a methodologically sound approach to the practicality and accessibility of exposure therapies for anxiety disorders. This paper investigates the application of Virtual Reality Exposure Therapy (VRET) to treat agoraphobia, focusing on two pivotal research questions derived from identified gaps in current therapeutic approaches. The experimental results confirm the efficacy of VR settings in eliciting significant physiological and psychological responses from participants, substantiating the VR scenarios' potential as a therapeutic tool. This study contributes to the broader discourse on the viability and optimization of VR technologies in clinical settings, offering a methodologically sound approach to the practicality and accessibility of exposure therapies for anxiety disorders.